Relationships Between Livestock Damages and Large Carnivore Densities in Sweden - Dalerum, Fredrik; Selby, Liam O. K.; Pirk, Christian W. W. (Frontiers in Ecology and Evolution, 2020)
Promoting co-existence between humans and their physical and ecological environment, including wildlife, has been given an increased importance due to a recent shift of society to become environmentally sustainable. However, humans and large carnivores have been in conflict throughout history. One of the most prominent reasons for this conflict is damages to livestock and domestic animals. Population reduction or even local eradication has often been used as a damage mitigation strategy. However, for population reduction to be an effective tool in limiting carnivore damages, number of damages need to be positively related to carnivore densities. Sweden is a country in northern Europe with frequent human-carnivore conflicts, spurred by an intense and polarized public debate. Here, we use a 20-year data set on brown bear (Ursus arctos), Eurasian lynx (Lynx lynx) and wolf (Canis lupus) and their damages in Sweden to evaluate if temporal variation in densities has caused an equivalent variation in the number of damages to cattle, sheep and domestic dogs, if such relationships differ between the carnivore species and damage types, and if there were geographic scale dependencies in these relationships. We observed contradictory effects of large carnivore densities on damages, which included both positive and negative effects of density on damages depending on carnivore species, damage type, geographic area and spatial scale. These results suggest that population reduction may not necessarily be an effective method for limiting large carnivore damages. They also highlight that large carnivore damages can be highly context dependent. Damage mitigation strategies therefore need to be very flexible over time and space. Because of the observed discrepancies in our results, we suggest that the effects large carnivore densities have on damages are highly context dependent, and that other factors than the size of local or regional carnivore populations in many cases may be more important damage determinants. We recommend further studies identifying the contexts in which large carnivore densities influence damages to livestock and domestic animals, as well as studies aimed at identifying other factors that may be related to the number of damages.